Cleaning of contaminated MFM probes using a BOPP film and external magnetic field. (June 2017) - Zhang, Chao; Liu, Jinyun; Meng, Qingling; Zhang, Wenxiao; Wang, Ying; Li, Dayou; Wang, Zuobin
Highlights: A method to clean contaminated magnetic force microscope (MFM) probes is presented. A BOPP film and a magnetic field were used to clean the contaminated probes. An MFM was used to study the cleaning process of contaminated probes. A scanning electron microscope (SEM) was used to examine the cleaning results. This method is effective for the cleaning of contaminated MFM probes. Abstract: When magnetic samples are tested with a magnetic force microscope (MFM), the probe tip can inevitably be contaminated and magnetic particles are often adhered to the tip surface. The probe with magnetic contamination will seriously affect the quality of morphological and magnetic imaging. In the work, a method for the cleaning of contaminated magnetic probe tips was developed by the use of a biaxially-oriented polypropylene (BOPP) film together with an external magnet field in an MFM system. In the experiments, an MFM system was used for manipulating the tip to push into the BOPP film with a depth of 50–100 nm under a magnetic field and hold for 5 s, and the relationships between loading forces and separating forces were studied. The scanning electron microscope (SEM) images have shown that the use of the BOPP film together with an external magnet field is effective for the cleaning of contaminated MFM probes. This method can greatly improve the quality of magnetic imaging, prolong the service life of magnetic probes and reduce the experimental costs in many MFM applications.